1996
DOI: 10.1080/00913847.1996.11947914
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Is Medicine

Abstract: Exercise is becoming more widely used to prevent and treat the diseases that are most prevalent in the United States: coronary artery disease, stroke, hypertension, diabetes, arthritis, osteoporosis, dyslipidemia, obesity, depression, cancer, and chronic obstructive pulmonary disease. However, physicians need more training in how to make best use of this powerful therapy. Physicians can successfully encourage activity by giving patients a written exercise prescription along with printed advice on how to design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In addition to performance, the abovementioned practical applications were also relevant from a health perspective. The role of exercise in the prevention and treatment of diseases (e.g., coronary artery disease, stroke, hypertension, diabetes, arthritis, osteoporosis, dyslipidemia, obesity, depression, cancer, and chronic obstructive pulmonary disease) has been well recognized [47]. The findings of the present study can aid physicians prescribing endurance exercise considering sex and age [48].…”
Section: Discussionmentioning
confidence: 84%
“…In addition to performance, the abovementioned practical applications were also relevant from a health perspective. The role of exercise in the prevention and treatment of diseases (e.g., coronary artery disease, stroke, hypertension, diabetes, arthritis, osteoporosis, dyslipidemia, obesity, depression, cancer, and chronic obstructive pulmonary disease) has been well recognized [47]. The findings of the present study can aid physicians prescribing endurance exercise considering sex and age [48].…”
Section: Discussionmentioning
confidence: 84%
“…While it has been suggested that physical fitness may serve as a nonpharmacological way of treating the effects of stress (Elrick 1996), the relationship between these two concepts is not clear. Research that investigates the effect of physical fitness on the stress response has focused, in part, on whether fit individuals have a blunted reaction to a laboratory or naturally occurring stressor (Brooke and Long 1987;Van Doornen and De Geus 1989;Choi and Salmon 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Aerobic fitness has also been associated with decreased plasma catecholamine levels during both physical and psychological stress (Sothmann and others 1987). A more recent report suggests that exercise consisting of aerobic, anaerobic, and conditioning components may serve as a treatment and/or prevention for illnesses such as heart disease, cancer, stroke, hypertension, chronic obstructive pulmonary disease, diabetes, and osteoporosis (Elrick 1996).…”
mentioning
confidence: 99%
“…Whether exercise activates BAT or induces its recruitment is uncertain 9 . Exercise is an effective aid in preventing many physical 10 and mental 11 diseases 12 , including adiposity, but its effect on BAT remains controversial 1315 . Case-control studies have shown that the BAT 18 F-fluorodeoxyglucose ( 18 F-FDG) uptake of endurance-trained men 16 and women 17 [high levels of maximum oxygen uptake (VO2max)] is lower than that of sedentary and non-athlete controls [low VO2max].…”
Section: Introductionmentioning
confidence: 99%